2002
DOI: 10.1021/ic025896i
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Halide Complexes with 1,3-Propanebis(diphenylphosphine) and Heterocyclic Thione Ligands:  Crystal and Electronic Structures (DFT) of [CuCl(pymtH)(dppp)], [CuBr(pymtH)(dppp)], and [Cu(μ-I)(dppp)]2

Abstract: Reaction of copper(I) chloride or bromide with equimolar amounts of the diphos ligand 1,3-propanebis(diphenylphosphine) and a heterocyclic thione (L) in acetonitrile/methanol solvent afforded mononuclear complexes of the type [CuX(dppp)(L)] with the diphosphine ligand acting as a chelating ligand. In contrast, copper(I) iodide under the same conditions gave the dimeric complex [Cu(mu-I)(dppp)](2), which contains doubly bridging iodo ligands. The structures of three complexes, namely, [CuCl(pymtH)(dppp)], [CuCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 35 publications
4
45
0
1
Order By: Relevance
“…121-126°. [29][30][31][32][33][34][35][36][37][38] Complex [(CuBr(κ 1 -S-l-NMe)(PPh 3 ) 2 .CuBr(PPh 3 ) 2 ] (2) has two different four and three coordinated independent molecules in the unit cell. The latter moiety CuBr(PPh 3 ) 2 [47] The bond parameters of complexes under study are similar to those reported for LЈ-NH ligand [47] and other heterocyclic-2-thiones.…”
Section: Mononuclear Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…121-126°. [29][30][31][32][33][34][35][36][37][38] Complex [(CuBr(κ 1 -S-l-NMe)(PPh 3 ) 2 .CuBr(PPh 3 ) 2 ] (2) has two different four and three coordinated independent molecules in the unit cell. The latter moiety CuBr(PPh 3 ) 2 [47] The bond parameters of complexes under study are similar to those reported for LЈ-NH ligand [47] and other heterocyclic-2-thiones.…”
Section: Mononuclear Complexesmentioning
confidence: 99%
“…The latter moiety CuBr(PPh 3 ) 2 [47] The bond parameters of complexes under study are similar to those reported for LЈ-NH ligand [47] and other heterocyclic-2-thiones. [29][30][31][32][33][34][35][36][37][38] …”
Section: Mononuclear Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, formation of halide bridges has been found to be favored for the "soft" iodide but not for the "harder" chloride ligands, whereas both bridging and terminal bonding modes were observed for the bromide ligands since bromide lies on the borderline between soft and hard bases [10]. The luminescent properties of copper(I) halide aggregates have been extensively studied by Ford et al, who showed that luminescent behaviour and geometries of the aggregate are strictly related [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A number of heteroligand Cu I complexes containing both aryl-substituted pnictides and cyclic thioureas or pyridinethiolates have also been described. [21][22][23] A combination of these two types of ligands might lead to interesting and unusual photophysical and electrochemical properties. [24] In this contribution we describe new heteroligand complexes of Cu I …”
Section: Introductionmentioning
confidence: 99%